High-intensity intermittent cycle ergometer exercise: Effect of recovery duration and resistive force selection on performance - Baker, J. S.; van Praagh, M.; Gelsei, M.; Thomas, M.; Davies, B. (Research in Sports Medicine, 2007)
The purpose of this study was to compare the exercise performance and postexercise recovery of 8 male subjects using four different maximal high-intensity intermittent cycle ergometry protocols. Resistive forces were calculated by multiplying fat-free mass (FFM) or total-body mass (TBM) by 0.75 g.kg-1. Rest periods between successive sprints were 30 s (R30) or 60 s (R60) duration. Higher pedal velocities were recorded using FFM as opposed to TBM (P < 0.05). Rest intervals of R60 (P < 0.05) influenced the peak power output values (903.88 ± 184.01W; TBM/R30 vs. 852.98 ± 209.68W; FFM/R30 vs. 965.64 ± 177.48W; TBM/R60 vs. 968.66 ± 173.70W; FFM/R60). Diastolic blood pressure (DBP) was lower than resting values (P < 0.05) postexercise in all protocols. These findings demonstrate that power outputs rely on resistive force selection and recovery duration, and that high-intensity exercise may provide an alternative to aerobic activity in the management of hypertension.